Foundations of political economy : some early Tudor views on state and society - Wood, Neal (University of California Press, 1994)
Conventional wisdom claims that the seventeenth century gave birth to the material and ideological forces that culminated in the Industrial Revolution and the rise of capitalism. Not true, according to Neal Wood, who argues that much earlier reformers--Dudley, Starkey, Brinklow, Latimer, Crowley, Becon, Lever, and Thomas Smith, as well as the better-known More and Fortescue--laid the groundwork by fashioning an economic conception of the state in response to s.
Keywords: Economics -- Great Britain -- History -- To 1800.; Political science -- Great Britain -- History -- 16th century.; Économie politique -- Grande-Bretagne -- Histoire -- Jusqu'à 1800.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; HISTORY / Europe / General; Economics; Political science; Great Britain; Economische filosofie.; Politieke ideeën.; Verenigd Koninkrijk van Groot-Brittannië en Noord-Ierland.; Business & Economics.; Economic Theory.; To 1800; History